Chemical Contamination of California Drinking Water - Russell, Hanafi H. (1987)
Drinking water contamination by toxic chemicals has become widely recognized as a public health concern since the discovery of 1,2-dibromo-3-chloropropane in California's Central Valley in 1979. Increased monitoring since then has shown that other pesticides and industrial chemicals are present in drinking water. Contaminants of drinking water also include naturally occurring substances such as asbestos and even the by-products of water chlorination. Public water systems, commercially bottled and vended water and mineral water are regulated, and California is also taking measures to prevent water pollution by chemicals through various new laws and programs.